Intellectual property in the global arena : jurisdiction, applicable law, and the recognition of judgments in Europe, Japan and the US - Basedow, Jürgen, 1949-; Kono, Toshiyuki; Metzger, Axel, 1971- (Materialien zum ausländischen und internationalen Privatrecht ;, 2010)
The private international law of intellectual property is currently much debated both in Europe and abroad. Art. 8 of the Rome II Regulation of 2007, which codifies a territorial approach for the infringement of intellectual property, has provoked an intensive discussion in Europe as to whether the lex loci protection is still appropriate for intellectual property litigation in the age of worldwide networks. A condensed outcome of this debate is summarized in the Principles for Conflict of Laws in Intellectual Property" (CLIP Principles) drafted by the European Max Planck Group on Conflict of Laws in Intellectual Property (CLIP), published recently in a second preliminary draft. On the international scale, the American Law Institute's Intellectual Property: Principles Governing Jurisdiction, Choice of Law, and Judgments in Transnational Disputes" of 2007 (ALI Principles) are the focal point of the debate. A Japanese project (Transparency Proposal") was finalized in 2009. This volume provides a comparative analysis of the three proposals. It compiles papers presented at an international conference held in Tokyo in May 2009.